The big over easy - Fforde, Jasper; Prebble, Simon (New York : Penguin Audio, 2005)
Detective Jack Spratt, recently unable to convict three wily pigs in he murder of a certain wolf, meets the challenge of a new case when Humpty Dumpty is found shattered to death beneath a wall in a shady part of town.
Compact discs.
"A nursery crime"--Cover.
Unabridged.
Read by Simon Prebble.
Keywords: Nursery rhymes -- Adaptations; Detective and mystery fiction; Fantasy fiction; Audiobooks